The dietary perceptions and practices among community-dwelling elderly - Zainudin, Norain; Hamirudin, Aliza Haslinda; A. Rahman, Nor Azlina; Sidek, Suriati (Nutrition Society of Malaysia, 2017)
The elderly population is increasing worldwide including Malaysia. This projected growth in the elderly population has the potential to place significant burdens on healthcare services. Ensuring adequate nutrition needs and proper intake of elderly is crucial for the maintenance of health, functional independence and quality of life. Thus,a deeper understanding of elderly views on dietary practices are greatly needed. The purpose of this study was to gain an insight into perceptions of community-dwelling Malaysian elderly on their dietary practices by using qualitative research method. A qualitative study was conducted using semi-structured interviews among twenty one individual aged 60 years and above which were recruited from felda settlements around Kuantan, Pahang. Thematic analysis was performed on transcriptions of audio-recorded interviews and was assisted using the NVivo software. The interviews ceased when data saturation was achieved. Thematic analysis revealed five themes that represent elderly dietary practices. These included:1) Impact of aging on meal pattern; 2) Decreased food intake associated with physiological changes; 3)Influence of health condition on food intake; 4) Healthfulness of certain foods influence dietary intake and 5)Social factors influenced dietary practices. Results of this study provide better view on community-dwelling elderly challenges for the maintenance of good nutritional health. It is pivotal to pay attention to the individual problems and the associated factors that may influence their dietary practices in order to provide action for achieving the good nutritional status.